Overview of Wnt/β-Catenin Pathway and DNA Damage/Repair in Cancer - Silvina B. Nadin; F. Darío Cuello-Carrión; Niubys Cayado-Gutiérrez; Mariel A. Fanelli (Biology)
The Wnt/β-catenin pathway takes part in important cellular processes in tumor cells, such as gene expression, adhesion, and survival. The canonical pathway is activated in several tumors, and β-catenin is its major effector. The union of Wnt to the co-receptor complex causes the inhibition of GSK3β activity, thus preventing the phosphorylation and degradation of β-catenin, which accumulates in the cytoplasm, to subsequently be transported to the nucleus to associate with transcription factors. The relationship between Wnt/β-catenin and DNA damage/repair mechanisms has been a focus for the last few years. Studying the Wnt/β-catenin network interactions with DNA damage/repair proteins has become a successful research field. This review provides an overview of the participation of Wnt/β-catenin in DNA damage/repair mechanisms and their future implications as targets for cancer therapy.